Health Risk Perception, Demand, and Willingness to Pay for Weight Reduction - Fu, Tsu-Tan; Lin, Yih-Ming (Taipei Economic Inquiry, 2014)
This study investigates factors that affect sample respondents' demand for weight reduction, incorporating the obesity health risk perception, and further develops a means to estimate their willingness to pay (WTP) for a therapy of obesity prevention using survey data of CVDFACTS. As for the decision to participate in an obesity prevention therapy, we find that gender, age, income and job status, BMI, and family illness history are important and significant determinants for respondents. In addition, the results also present that the concerns on social and martial relations as affected by obesity are important and significant determinants. The doubled-bound dichotomous choice model estimates the respondents' WTP. The model estimates that the average willingness to pay for an obesity prevention therapy, which could reduce weight by 5 kilograms in 3 months, is NT$3,388 for the male and NT$4,689 for the female sample respondents, respectively. Furthermore, this study notes that age, income, the concern that work achievement is affected by obesity, and those who have tried to control their weight are important and significant determinants of the WTP. The results of the profile analysis suggest that obese females with high income, high health risk perception, and who have tried to control their weight are the most likely to be willing to pay the greatest amount for the weight-reduction therapy. [PUBLICATION ABSTRACT]